Perceptions of PAI Students on the Use of ChatGpt for Writing Scientific Papers at K.H Abdurrahman Wahid State Islamic University - Lestari, Salsa Dwi; Emiliana , Nailul Uly; As'syifa , Rahma Mutiara (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on the world of education. One form of AI technology currently widely used is ChatGPT, an artificial intelligence model capable of assisting users in processing information, answering questions, solving problems, and even composing academic texts. The presence of ChatGPT has generated diverse responses, especially among students who are beginning to utilize it in their learning. This study aims to explore the perspectives of Islamic Education (PAI) students on the use of ChatGPT in the process of writing scientific papers. With the advancement of information technology, artificial intelligence-based tools such as ChatGPT are beginning to be utilized in the academic world. The research method used was qualitative, with data collection through interviews and questionnaires. The results indicate that PAI students have diverse views on ChatGPT. Most students believe that ChatGPT can help them find references, speed up the writing process, and generate new ideas. However, there are also concerns about the authenticity of their work and the potential for plagiarism. This research is expected to provide insights for educators and educational institutions in understanding the impact of technology use in academic writing and provide recommendations for more ethical and effective use.